KONSEP PENDIDIKAN PERSPEKTIF GENDER MENURUT KH. HUSEIN MUHAMMAD - admin, admin; Fitriah, Fitriah (Prodi PAI IAILM Suryalaya, 2021)
The background of this research arises when gender differences have given birth to differences in social roles. Sometimes these social roles are standardized by the community, so there is no opportunity for women or men to change roles. In Javanese tradition, this standardization of roles is expressed in many proverbs, for example, women are the conco wingking of the man who becomes her husband. He is a life partner whose role is always behind. This proverb also implies that women's duties are behind them. In Javanese culture, the term